A novel intuitionistic fuzzy decision-making framework for sustainable site selection of solar panel waste recycling facilities - Yildirim, Betul; Ayyildiz, Ertugrul; Aydin, Nezir; Yıldırım, Betül (Elsevier Ltd, 2025)
Increasing global energy demand makes the transition to efficient and clean energy sources, such as solar energy, necessary. However, decommissioned solar panels generate hazardous waste, creating significant environmental challenges. Establishing an optimal location for solar panel waste recycling facilities is crucial to ensuring sustainability and compliance with environmental regulations. This study identifies and evaluates a detailed set of criteria, including environmental, economic, social, and technical aspects, critical for the site selection of solar panel waste recycling plants. This study offers the first methodical approach for solar waste management in Türkiye, confirming that growing solar energy investments align with sustainable waste treatment strategies. To handle the complexities of this process, an integrated methodology combining an improved Intuitionistic Fuzzy Indifference Threshold-Based Attribute Ratio Analysis (IF-ITARA) and Intuitionistic Fuzzy Evaluation based on Distance from Average Solution (IF-EDAS) is proposed. IF-ITARA is developed and introduced to the literature to provide a more precise determination of criteria weights, while IF-EDAS ranks the five potential sites in Turkiye, including Izmir, Konya, Kayseri, Antalya, and Sanliurfa, based on these weights. This approach effectively manages uncertainties and subjectivity in decision-making by incorporating intuitionistic fuzzy logic, providing a robust and systematic evaluation. The findings show that the most significant factor in the site selection process of the solar panel waste recycling plant is the legal and regulatory environment. The results offer valuable insights for policymakers and stakeholders involved in solar waste management and sustainable infrastructure planning. This study not only advances the application of decision-making approaches but also contributes to the broader goal of promoting a circular economy in the renewable energy sector.
Keywords: Solar panel waste recycling; Sustainability; MCDM